NIV-NAVA versus NCPAP immediately after birth in premature infants: A randomized controlled trial - Lee Juyoung; Parikka Vilhelmiina; Oda Arata; Wallström Linda; Lehtonen Liisa; Soukka Hanna (ELSEVIER, 2022)
Objective: To evaluate whether noninvasive-neurally adjusted ventilatory assist (NIV-NAVA) decrease respiratory efforts compared to nasal continuous positive airway pressure (NCPAP) during the first hours of life.
Methods: Twenty infants born between 28+0 and 31+6 weeks were randomized to NIV-NAVA or NCPAP. Positive end-expiratory pressure was constantly kept at 6 cmH(2)O for both groups and the NAVA level was 1.0 cmH(2)O/mu V for NIV-NAVA group. The electrical activity of diaphragm (Edi) were recorded for the first two hours.
Results: Peak and minimum Edi decreased similarly in both groups (P = 0.98 and P = 0.59, respectively). Leakages were higher in the NIV-NAVA group than in the NCPAP group (P < 0.001). The neural apnea defined as a flat Edi for >= 5 s were less frequent in NIV-NAVA group than in NCPAP group (P = 0.046).
Conclusions: Immediately applied NIV-NAVA in premature infants did not reduce breathing effort, measured as peak Edi. However, NIV-NAVA decreased neural apneic episodes compared to NCPAP.